Phytochemical Constituents and In Vitro Antitrypanosomal Activity of Ethanol Seed Extract of Buchholzia Coriacea - Abubakar, A.; Jigam, A.A.; Kabir , A.Y.; Adefolaju, O.V. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2017)
The medicinal efficacy of Buchholzia coriacea seed extract was screened for possible anti-trypanosomal activity in vitro.Whole Buchholzia coriacea seeds were extracted with 80% ethanol (EtOH) to obtained crude extract. The flavonoid fractionwas extracted from crude ethanol extract using n-butanol and purified in column chromatography eluted with methanol. Thecrude extract and flavonoid fraction obtained were screened for in vitro antitrypanosomal activity by mixing 20 μl of bloodsample containing about 20-25 parasites per field with 5 μl of crude ethanol extract and flavonoid fraction separately at 20.0,2.0 and 0.2 mg/ml producing effective concentrations of 4, 0.4 and 0.04 mg/ml, respectively. Result indicated that flavonoidfraction of B. coriacea exhibited complete caesation of motility of T. b. brucei within 60 minutes at concentrations of 4 and0.4 mg/ml while the crude ethanol extract recorded only reduction on parasite count and sluggishness in motility as comparedto untreated control. Differences in the amount of phytochemical present could probably be responsible for the observedantitrypanosomal activity. This study therefore provides scientific evidence for the traditional use of ethanol crude extract andflavonoid fraction of Bucholzia coriacea seed for the management of trypanosomosis.